2014
DOI: 10.1021/ac5028808
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Look Inside the Body: Minimally Invasive Infrared Analysis in Vivo

Abstract: Today's minimally invasive biosensors are often based on chemical reagents and suffer from, e.g., oxygen dependence, toxic reaction products, excess analyte consumption, and/or degradation of the reagents. Here, we show the first successful analyte quantification by means of a minimally invasive sensor in vivo, which does not use chemical reactions. The concentration of glucose is determined continuously in vivo using transcutaneous, fiber-based mid-infrared laser spectroscopy. When comparing the infrared data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…After multiple refinement steps of the method, [203][204][205] Vrančić et al presented a minimally invasive fiber-based sensor for continuous in vivo glucose monitoring. 206 Here, a pulsed, nontunable laser operated at 1030 cm À1 was used with a pyroelectric detector. The silver halide fiber with a 20 mm gap was implanted in a rat's neck and changes of the glucose level were continuously monitored in the ISF after injections of glucose or insulin.…”
Section: Analysis Of Bodily Fluidsmentioning
confidence: 99%
“…After multiple refinement steps of the method, [203][204][205] Vrančić et al presented a minimally invasive fiber-based sensor for continuous in vivo glucose monitoring. 206 Here, a pulsed, nontunable laser operated at 1030 cm À1 was used with a pyroelectric detector. The silver halide fiber with a 20 mm gap was implanted in a rat's neck and changes of the glucose level were continuously monitored in the ISF after injections of glucose or insulin.…”
Section: Analysis Of Bodily Fluidsmentioning
confidence: 99%
“…Vrancić et al [13] could increase the sensitivity to NEC values as low as 4 mg/dL using also a fiber-based sensor setup with a discrete frequency Fabry-Perot QCL and an optical path length of 30 µm. Vrancić et al [14] also performed the first in vivo experiments using this fiber-based sensor in an animal-model. With a prediction accuracy of 7 mg/dL and a sampling duration of 6 s over a period of several hours, they showed that the method is in principle well suited for in vivo use.…”
Section: State Of the Art In Mid-infrared Based Glucose Monitoringmentioning
confidence: 99%
“…Besides this vast progress in the field of in vitro analytics, Vrancić et al [14] still remain the only group that investigated this method in vivo and built a basis for continuous glucose monitoring in diabetes patients. They used silver/ silver halide fibers in transmission with a microfabricated gap in the fiber to be filled by the liquid via diffusion processes.…”
Section: State Of the Art In Mid-infrared Based Glucose Monitoringmentioning
confidence: 99%
“…These researchers irradiated the human palm or wrist with an EC-QCL and measured the backscattered light using a hollow optical fiber [14] or an integrating sphere [15]. Furthermore, some groups have used photoacoustic techniques to measure glucose concentrations in the interstitial fluid of human skin [24]. The authors successfully measured glucose concentrations in the interstitial fluid of rats by using a fiber probe with small gaps that was filled with the sample material.…”
Section: Introductionmentioning
confidence: 99%